Girl in the water : a true story of sibling abuse - Kilgore, Nancy, 1949- (Health Communications, Inc., 2013)
"When Nancy Kilgore was nine years old, her eleven-year-old sister Sherry led her into the scorching midday sun, tied her to a chair, and taped her eyelids to her eyebrows with electrical tape, leaving Nancy helpless for hours to stare into a blinding blue sky. For years, Sherry physically tortured her younger sister and threatened to kill her if the cruelty was revealed. Each time Nancy walked into her own bedroom she would have to repeat self-deprecating passwords: "I am ugly and stupid." "I am ugly, stupid, and no one loves me." "Please may I come in?" Girl in the Water details the most shuttering examples of sibling abuse, the untold secret in millions of homes. Each year, 19 million children are abused by their siblings and well over 80 million adults have suffered this type of abuse. With vivid imagery and heartbreaking accounts, Kilgore leads readers on a journey into the prison she was born into, where she is confronted with her childhood dreams, family bonds, coming of age in the shadow of terror, and the complex after-effects of bullying and sibling abuse that followed her into adulthood. Struggling to piece together her haunted past before it consumed her, Kilgore shares her inspiring metamorphosis and victorious battle from a fragile, shattered survivor to that of an eventual speaker and activist. Girl in the Water is the story of one woman, with a phoenix-like power, who came up against all odds and won. Her story will resonate with millions of adult sibling-abuse survivors who have never felt free to tell their stories. until now"--